2021
DOI: 10.1108/mhrj-10-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes among health-care workers during the COVID-19 outbreak in Iran

Abstract: Purpose The increasing prevalence of coronavirus disease (COVID-19) is a global crisis that leads to physical and psychological outcomes for health-care workers, so this study aims to investigate the mental health outcomes (including general health, generalized anxiety disorder and posttraumatic stress disorder) in health-care workers in Rafsanjan, Iran. Design/methodology/approach By using convenience sampling, this cross-sectional study was conducted on 332 health-care workers working in public hospitals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The current study compared nurses working in all wards (intensive care, emergency, medical, and so on) at two different times (before and during the first wave of the COVID-19 pandemic), but Zhang only studied intensive care unit nurses, while Gómez-Urquiza studied emergency nurses, and no comparison was made in both studies. (Zakeri et al, 2021a;Zheng et al, 2021). Doo et al (2021) revealed that nurses working in the COVID-19 wards had higher anxiety and depression than nurses working in other wards (Doo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study compared nurses working in all wards (intensive care, emergency, medical, and so on) at two different times (before and during the first wave of the COVID-19 pandemic), but Zhang only studied intensive care unit nurses, while Gómez-Urquiza studied emergency nurses, and no comparison was made in both studies. (Zakeri et al, 2021a;Zheng et al, 2021). Doo et al (2021) revealed that nurses working in the COVID-19 wards had higher anxiety and depression than nurses working in other wards (Doo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the most common behavioral disorders, according to the World Health Organization, and is associated with low mood, loss of interest, feelings of guilt and worthlessness, changes in energy, concentration, sleep, and appetite (Vilagut et al, 2016). According to Zakeri et al (2021a), anxiety, stress, and depression were very common among the frontline workers caring for the COVID-19 patients (Zakeri et al, 2021a). Cai et al (2020) studied 534 physicians, nurses, and primary care providers in Hubei State and found that they were under a lot of stress during the COVID-19 outbreak (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fear of the unknown reduces the perception of immunity in humans and has always been stressful for them. Studies have reported high levels of anxiety and stress in the prevalence of COVID-19 disease [ 12 , 13 ]. Anxiety is defined as a feeling of worry, anger, or dissatisfaction with something with an uncertain outcome [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…is has caused acute problems and even death of some patients [23]. Studies have reported a high prevalence of fear and anxiety caused by COVID-19 [24,25]. Physicians' attention to the mental and psychological condition of patients and involvement of the patients in the invasive procedures during the outbreak of COVID-19 are among the most important challenges facing the medical system that can have a direct impact on patient survival.…”
Section: Discussionmentioning
confidence: 99%